Contrato de gestão : considerações sobre a sua viabilidade na administração educacional - Oliveira, Jose Almi de (1996)
This essay consists of the hypothesis that the current stnlcture of education is highly rigid, bureaucratic an centralized. The solution can be in a different type of manab'11lent in which contemplates a major descentralization and autonomy of school. On the other hand, it admits that the participation of all proffessionals involved in the education process, as welI as, the students, student's parents and other representative segments of community is fundamental in order to have, an efficacious and effective school, in which can offer, as a product, a good quality of teaching, fulfiling alI the society's expectation. So, this work has the aim to investigate the possibility of the managment contract implementation on the educational area, considering it as a tool that can make possible the administrative descentralization and concede more autonomy to the schools with the social participation, while it simultaneously allows that, the govemement has good instruments ready for guarantee an equity of entire system.